Treatment with the Self-Discovery Camp (SDiC) improves Internet gaming disorder. (January 2017) - Sakuma, Hiroshi; Mihara, Satoko; Nakayama, Hideki; Miura, Kumiko; Kitayuguchi, Takashi; Maezono, Masaki; Hashimoto, Takuma; Higuchi, Susumu
Abstract: Introduction: Internet gaming disorder (IGD) is a novel behavioral addiction that influences the physical, mental, and social aspects of health due to excessive Internet gaming. One type of intensive treatment for IGD is the therapeutic residential camp (TRC), which comprises many types of therapies, including psychotherapy, psychoeducational therapy, and cognitive behavioral therapy. The TRC was developed in South Korea and has been administered to many patients with IGD; however, its efficacy in other countries remains unknown. We investigated the efficacy of the Self-Discovery Camp (SDiC), a Japanese version of a TRC, and the correlations between individual characteristics and outcome measures. Methods: We recruited 10 patients with IGD (all male, mean age = 16.2 years, diagnosed using the DSM-5) to spend 8 nights and 9 days at the SDiC. We measured gaming time as well as self-efficacy (using the Stages of Change Readiness and Treatment Eagerness Scale, a measure of therapeutic motivation and problem recognition). Results: Total gaming time was significantly lower 3 months after the SDiC. Problem recognition and self-efficacy towards positive change also improved. Furthermore, there was a correlation between age of onset and problem recognition score. Conclusions: Our results demonstrate the effectiveness of the SDiC for IGD, especially regarding gaming time and self-efficacy. Additionally, age of onset may be a useful predictor of IGD prognosis. Further studies with larger sample sizes and control groups, and that target long-term outcomes, are needed to extend our understanding of SDiC efficacy. Highlights: We devised a therapeutic residential camp for Internet gaming disorder. This Self-Discovery Camp led to decreased gaming time at a 3-month follow-up. Problem recognition and self-efficacy scores similarly increased after the camp. Onset age of Internet gaming disorder and problem recognition were correlated.